RTHP-18. PROSPECTIVE PHASE II RANDOMIZED TRIAL COMPARING PROTON THERAPY VS. PHOTON IMRT FOR NEWLY DIAGNOSED GBM: SECONDARY ANALYSIS COMPARISON OF GENDER AND NEUTROPHIL-LYMPHOCYTE RATIO (NLR) IN GBM OUTCOMES. (11th November 2019) - Randall, James; Al Feghali, Karine; Wefel, Jeffrey; Grosshans, David; Dibaj, Seyedeh; Milton, Denai; McAvoy, Sarah; Li, Jing; McGovern, Susan; McAleer, Mary; Ghia, Amol; Paulino, Arnold; et al.
Abstract: BACKGROUND: While glioblastoma (GBM) is more prevalent in males, studies show that females with GBM tend to have longer overall survival (OS) than males. Pretreatment neutrophil to lymphocyte ratio (NLR) has also proven to be prognostic in GBM, with lower NLR having favorable outcomes. This secondary analysis of a prospective randomized trial of proton vs. photon intensity modulated radiotherapy aims to explore the interaction of gender and NLR on GBM outcomes. METHODS: Analysis was performed on the full patient population. Kaplan-Meier methods estimated OS with censoring at last follow-up for those who were alive. Univariate (UVA) and multivariate (MVA)Cox proportional hazards models assessed predictors of OS. RESULTS: Of 90 patients, 77 were included (43 males; 34 females) with median age of 52 years (range: 26–82 years). Median OS was longer for females than males (30.7 vs 18.2 months, p=0.004). On UVA, patients with NLR below median value (NLR= 3.1) tended to have longer OS than those above median, though not meeting statistical significance (23.1 vs. 17.9 months, p=0.051). Difference in OS was statistically significant in females (OS 36.4 months NLR >median vs. 16.7 months NLR< median, p=0.002), but not in males (OS 17.8 months NLR >median vs. 19.1 NLR< median, p=0.95). MVA analysis was consistent, with female gender predicting reduced hazard ratio (HR) (0.28, p=0.034) and females with below median NLR showing a reduced HR over those with above median (0.28, p=0.005). Again, males did not benefit (HR 0.90, p=0.77). CONCLUSION: Consistent with prior publications, females and all patients with lower pre-treatment NLR with newly diagnosed GBM had longer OS. However, combining these two factors revealed that the benefits from lower pre-treatment NLR were conferred only in females with no impact on males. This different impact of NLR between genders may suggest innate immune differences in gender during response to malignancy.